Islamic Sleep Ritual Activity (ISRA) Intervention Improving Sleep Quality, Physical and Psychological Comfort for Pregnant Women in the Third Trimester - Zainiyah, Zakkiyatus Zainiyah; Hapsari, Veni Dwi; Fitriah, Fitriah; M. Hasinuddin, M. Hasinuddin (JURNAL KEBIDANAN, 2025)
Psychological changes in the third trimester are increasingly complex due to the growing condition of pregnancy, physical discomfort, worry, fear, indecision, and doubt about the condition of the pregnancy before childbirth so pregnant women need psychosocial support from husbands, families, and health workers. The study aimed to analyze the differences in Islamic Sleep Ritual Activity (ISRA) Intervention to Improve Sleep Quality and Physical and Psychological Comfort of Pregnant Women in Time Three. The research method of the non-equivalent control group design, the population is pregnant women in the third trimester in the working area of Alas Kembang Bangkalan village in 2024 as many as 48 people. Physiological pregnancy inclusion criteria, and exclusion criteria: Pregnant women who refuse to be researched and pregnant women who experience complications, use simple random sampling. The instrument used is a questionnaire using a value scale. Statistical tests use the paired t-test and the Wilcoxon test. The ISRA intervention study's results can significantly affect maternal sleep quality p 0.000 or 0.05. There is a significant difference between the physical comfort of pregnant women before and after being given the ISRA intervention p 0.001 or 0.05. The implementation of ISRA in the pregnant women's care program in the third trimester is highly recommended to provide a sense of comfort and quality of sleep to all pregnant women, and it needs to be continued for all pregnant women.